(The Effect Of Reconstitution Temperature For Local Isolates Of Enterobacter sakazakii (Cronobacter sp.) from Powdered Infant Formula and Weaning Food) - Ramadhani Meutia, Yuliasri; Dewanti-Hariyadi, Ratih; -, Estuningsih (Warta Industri Hasil Pertanian, 2009)
Enterobacter sakazakii (recently know as novel genus Cronobacter sp.) is opportunistic bacteria which can cause severe meningitis in neonates. Eight isolates of E.sakazakii which previously isolated from powdered infant formula (PIF) and weaning food were tested foe their ability to survive during reconstitution with water having various temperatures, and their fate during hang time in comparison with 7 isolates previously described by Estuningsih and E. sakazakii ATCC 352/7. reconstitution with 100 C water decreased he number of bacteria of most isolates to undetectable level, while with 40 C and 4 C water did not reduce the bacterial number significantly. Using water of 70 C, reconstitution decreased the number of bacteria of 10 isolates to undectable levels; however 6 isolates survived the reconstitution temperatures. The hang time test showed that some bacteria which were not detected after reconstitution with 70 C water became detectable after 2 hours. Those surviving reconstitution with 70 C well during hang time for 2 to 8 hours.